Multiple Familial Trichoepithelioma: A Rare Case Report Spanning Three Generations - Ramkumar, Madhumita; Vijaya Kumar,; M, Kandaswamy; A, Arunima; Paul, Sohini (Nepal Journal of Dermatology, Venereology & Leprology, 2026)
Multiple familial trichoepithelioma (MFT) is an uncommon, benign, adnexal tumor with an autosomal dominant inheritance pattern. It manifests as multiple, tiny, firm, skin-colored papules typically on the face. This case series describes five affected individuals across three generations, highlighting the clinical features, diagnostic challenges, and management considerations. Despite its benign nature, the condition carries significant cosmetic and psychological implications. Histopathology remains the gold standard for diagnosis, distinguishing it from malignant mimickers. Various treatment options have been explored, including surgical excision, laser therapy, radiofrequency ablation, topical agents like imiquimod, and electrosurgical techniques, with varying degrees of success. However, recurrence remains a challenge, and treatment depends on the degree of the disease and patient preference. Given the rarity of MFT, increasing awareness among clinicians is crucial for early recognition and appropriate management. This report emphasizes the importance of differentiating trichoepithelioma from other cutaneous neoplasms to prevent unnecessary interventions and optimize patient outcomes.